The Role of User Involvement in Deployment of Artificial Intelligence : CASE: Natural Language Processing in Customer Service - Peltomaa, Paula (My University, 2020)
Increasing numbers of artificial intelligence solutions in business simultaneously increasing the num-ber of people affected by artificial intelligence. Through involving users into the implementation of artificial intelligence solution leads into business benefits not only from the implemented technology but also by increasing the motivation on the users and adding their knowledge into the project and thus improving the quality of the solution. This study includes a case of implementing natural lan-guage processing solution into a Finnish customer service in the field of financial services. The case study focuses on why and how user involvement should be taken into account in an artificial intelli-gence solution implementation. This study builds its framework on technology acceptance model originally by Davis (1986) and the latter form of the model by Venkatesh & Bala (2008). User involvement here begins by empower-ing the users though communication, training and overall engaging the users with the technology and the project. This is the stage that users start to perceive the usefulness of the solution. This is followed by user participation where the users go from being passive receivers of information into active part of the project. They get hands-on experience through participating into the project work and start to ac-cept the technology as a part of their work. At this second stage users start forming their thoughts of the ease of use of the solution. At the final stage comes the users’ feeling of ownership of the technol-ogy. At this stage the users feel a sense of control of the technology and really adapt it into their work proactively, even teach how to use it for their peers.
Keywords: User involvement, technology acceptance model, natural language processing